Analysis of Cross-sectional and Longitudinal HLA and Anti-viral Responses After COVID Infection in Renal Allograft Recipients: Differences and Correlates. Issue 10 (2nd September 2022) - Girnita, Alin L.; Wang, Lin; Colovai, Adriana I.; Ahearn, Patrick; Azzi, Yorg; Menon, Madhav C.; Fernandez-Vina, Marcelo; Gebel, Howard M.; Steve Woodle, E.; Cravedi, Paolo; Maltzman, Jonathan S.; Akalin, Enver
Abstract : Background: Characterization of anti-HLA versus anti-severe acute respiratory syndrome coronavirus 2 (anti–SARS-CoV-2) immune globulin isotypes in organ transplant recipients after coronavirus disease 2019 (COVID-19) infection has not been reported. We aimed to determine changes in anti-HLA antibodies in renal transplant patients with COVID-19 and compare the immunoglobulin and epitope-binding pattern versus anti–SARS-CoV-2 antibodies. Methods: This is a cross-sectional study of 46 kidney transplant recipients including 21 with longitudinal sampling. Using a semi-quantitative multiplex assay, we determined immunoglobulin (Ig) M, IgA, IgG, and IgG1-2-3-4 antibodies against Class I and Class II HLA, and 5 SARS-CoV-2 epitopes including the nucleocapsid protein and multiple regions of the spike protein. Results: Fourteen of 46 (30%) patients had donor-specific anti-HLA antibodies (donor-specific antibody [DSA]), 12 (26%) had non-DSA anti-HLA antibodies and 45 (98%) had anti–SARS-CoV-2 antibodies. Most DSAs targeted HLA-DQ (71%), with a dominant IgG isotype and IgG1 subtype prevalence (93%), and/or IgG3 (64%), followed by IgG2 (36%). Comparatively, there was a higher prevalence of IgA (85% versus 14%, P = 0.0001) and IgM (87%, versus 36%, P = 0.001) in the anti–SARS-CoV-2 antibody profile, when compared to DSAs, respectively. Anti–SARS-CoV-2 antibody profile was characterized by increased prevalence of IgM and IgA, when compared to DSAs. The median calculated panel reactive antibody before COVID-19 diagnosis (24%) tended to decrease after COVID-19 diagnosis (10%) but it was not statistically significant ( P = 0.1). Conclusions: Anti-HLA antibody strength and calculated panel reactive antibody in kidney transplant recipients after COVID-19 do not significantly increase after infection. Although the IgG isotype was the dominant form in both HLA and SARS-CoV-2 antigens, the alloimmune response had a low IgA pattern, whereas anti–SARS-CoV-2 antibodies were high IgA/IgM. Abstract :